2018
DOI: 10.1016/j.gpb.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Reversible RNA ModificationN1-Methyladenosine (m1A) in mRNA and tRNA

Abstract: More than 100 modifications have been found in RNA. Analogous to epigenetic DNA methylation, epitranscriptomic modifications can be written, read, and erased by a complex network of proteins. Apart from N6-methyladenosine (m6A), N1-methyladenosine (m1A) has been found as a reversible modification in tRNA and mRNA. m1A occurs at positions 9, 14, and 58 of tRNA, with m1A58 being critical for tRNA stability. Other than the hundreds of m1A sites in mRNA and long non-coding RNA transcripts, transcriptome-wide mappi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
136
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(140 citation statements)
references
References 50 publications
4
136
0
Order By: Relevance
“…N 1 -methyladenosine (m 1 A) is a reversible modification in tRNA, mRNA and lncRNAs, even in mitochondrial transcripts, and is critical for tRNA stability, and translation of mitochondrial DNA-encoded proteins [134]. In nucleus, m 1 A modifications in pre-tRNA and pre-mRNA are catalyzed by tRNA methyltransferase 6/61A (TRMT6-TRMT61A) catalytic complex and are erased by ALKBH1 and ALKBH3, respectively [135,136].…”
Section: Rna M 1 a Modification In Gbmmentioning
confidence: 99%
“…N 1 -methyladenosine (m 1 A) is a reversible modification in tRNA, mRNA and lncRNAs, even in mitochondrial transcripts, and is critical for tRNA stability, and translation of mitochondrial DNA-encoded proteins [134]. In nucleus, m 1 A modifications in pre-tRNA and pre-mRNA are catalyzed by tRNA methyltransferase 6/61A (TRMT6-TRMT61A) catalytic complex and are erased by ALKBH1 and ALKBH3, respectively [135,136].…”
Section: Rna M 1 a Modification In Gbmmentioning
confidence: 99%
“…Different organs of the leaves, flowers and roots have differential m 6 A methylation, suggesting that m 6 A methylation plays an important role during development and differentiation (Wang et al, 2017). Besides which, more than 20 m 1 A sites are also identified in mitochondrial genes via using a transcriptome-wide analysis (Zhang and Jia, 2018). These findings unravel a new concept of mitoepitranscriptome, referring to dynamic regulation of gene expression by the modified mtRNAs.…”
Section: Mtrna Modificationsmentioning
confidence: 73%
“…Recent methodological advances have demonstrated that m1A is a transcriptome-wide modification [172,173]. Several members of the TRMT family (tRNA methyltransferase family) have already been shown to be m1A writers and additional writers are thought to exist [172][173][174]. Similar to m6A, m1A is reversible and can be demethylated by erasers ALKBH1 and 3 (alkB homolog 1 and 3) [173,175].…”
Section: N1-methyladenosine (M1a)mentioning
confidence: 99%